2009
DOI: 10.1007/s10495-009-0405-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple alphaII-spectrin breakdown products distinguish calpain and caspase dominated necrotic and apoptotic cell death pathways

Abstract: Apoptosis and oncotic necrosis in neuronal and glial cells have been documented in many neurological diseases. Distinguishing between these two major types of cell death in different neurological diseases is needed in order to better reveal the injury mechanisms so as to open up opportunities for therapy development. Accumulating evidence suggests apoptosis and oncosis epitomize the extreme ends of a broad spectrum of morphological and biochemical events. Biochemical markers that can distinguish between the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 66 publications
7
87
1
Order By: Relevance
“…Among these, recent studies have suggested that aII-spectrin breakdown products SBDP150 and 145, produced by calpain cleavage, have been linked to acute neuronal necrosis, while SBDP120, produced by caspase 3, has been linked to apoptotic cell death cascades. 41,122,[125][126][127][128][129][130][131] While these aII-spectrin breakdown products have been discussed within the context of neuronal damage, it is important to note that they have been associated with both TAI/DAI and its downstream target deafferentation and synaptic loss. 38,51,[132][133][134] In addition to spectrin breakdown products, other potential markers of axonal injury include various phosphoforms of the neurofilament-H subunit as well as cleaved tau suggesting damage to the axon cytoskeleton.…”
Section: Biomarkersmentioning
confidence: 99%
“…Among these, recent studies have suggested that aII-spectrin breakdown products SBDP150 and 145, produced by calpain cleavage, have been linked to acute neuronal necrosis, while SBDP120, produced by caspase 3, has been linked to apoptotic cell death cascades. 41,122,[125][126][127][128][129][130][131] While these aII-spectrin breakdown products have been discussed within the context of neuronal damage, it is important to note that they have been associated with both TAI/DAI and its downstream target deafferentation and synaptic loss. 38,51,[132][133][134] In addition to spectrin breakdown products, other potential markers of axonal injury include various phosphoforms of the neurofilament-H subunit as well as cleaved tau suggesting damage to the axon cytoskeleton.…”
Section: Biomarkersmentioning
confidence: 99%
“…23 With this method, the integrity of TDP-43 after neurotoxin induction was examined. In this study, no expected reduction in the intact TDP-43 was observed after either A23187 (20 mmol/L) or staurosporine (STS, 1 mmol/L) treatment.…”
Section: Tdp-43 Fragmentation Patterns By Calpain or Caspase-3mentioning
confidence: 99%
“…[59][60][61][62][63][64] The initial calpain-and caspase-mediated cleavages yield four breakdown products at about 145-150 kDa. 61,65,66 By applying a calpain inhibitor to our degradation model, we have successfully blocked degradation-induced spectrin breakdown, and by applying caspase cleavage-specific antibody (Asp1185) in western blotting, we did not detect the degradation-induced spectrin breakdown products (data not shown). These data suggest that the degradation-induced spectrin breakdown is calpain-mediated.…”
Section: Tissue Degradation Indicators J LI Et Almentioning
confidence: 99%